2015
DOI: 10.1155/2015/156509
|View full text |Cite
|
Sign up to set email alerts
|

Some Rare Earth Elements Analysis by Microwave Plasma Torch Coupled with the Linear Ion Trap Mass Spectrometry

Abstract: A sensitive mass spectrometric analysis method based on the microwave plasma technique is developed for the fast detection of trace rare earth elements (REEs) in aqueous solution. The plasma was produced from a microwave plasma torch (MPT) under atmospheric pressure and was used as ambient ion source of a linear ion trap mass spectrometer (LTQ). Water samples were directly pneumatically nebulized to flow into the plasma through the central tube of MPT. For some REEs, the generated composite ions were detected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…As a novel high‐frequency plasma generator at atmosphere pressure, the MPT ionization source was developed in 1985 at Jilin University of China, and substantial improvements were subsequently made at Indiana University . The traditional applications of the MPT were mainly focused on optical spectroscopy in the excitation source to analyze metallic and nonmetallic elements . Recently, the MPT has begun to be used as an ion source for ambient mass spectrometry.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a novel high‐frequency plasma generator at atmosphere pressure, the MPT ionization source was developed in 1985 at Jilin University of China, and substantial improvements were subsequently made at Indiana University . The traditional applications of the MPT were mainly focused on optical spectroscopy in the excitation source to analyze metallic and nonmetallic elements . Recently, the MPT has begun to be used as an ion source for ambient mass spectrometry.…”
Section: Introductionmentioning
confidence: 99%
“…Duan and coworkers systematically characterized microwave‐induced plasma desorption/ionization (MIPDI) mass spectrometry and suggested that MIPDI is a "hard‐soft" ion source . Zhu and coworkers used MPT‐MS for direct analysis of various metallic elements with a limit of detection (LOD) as low as 10 −8 g/L . Although ambient ionization methods have been developed for dozens of years, only several studies have been involved in drug abuse detection.…”
Section: Introductionmentioning
confidence: 99%
“…is electrophilic while metal ions are general electron donor. Usually, the nitrate radical comes from the air surroundings, but not the sample solutions [25,31].…”
Section: Results and Discusionsmentioning
confidence: 99%
“…More early, MPT had been used as a powerful light source and applied widely in spectrometric instruments [23,24]. Our previous studies [25] have showed that the MPT ion source coupled with a mass spectrometer can is a promising analytical tool in various fields. Adopting the desolvation unit, and injecting aqueous samples through the central-tube of MPT, the MPT mass spectrometry can be used to detect directly sensitively many kinds of metal elements in water, without tedious sample pretreatment.…”
Section: Introductionmentioning
confidence: 99%
“…These make MPT a suitable ionization source for desorption ionization of solid samples. Recently, protonated analytes in liquid samples were also produced by MPT [ 25 ]. Theoretically, the high temperature of MPT allows the observation of ambient thermal dissociation of the analyte ions produced by MPT sources.…”
Section: Introductionmentioning
confidence: 99%